Attitudes of Health Care providers toward Teamwork, Safety Climate and knowledge - Mahfoozpour, Soad; Mojdekar, Reyhaneh (Advances in Nursing & Midwifery, 2012)
ABSTRACT Background and aim : According to importance of occupational health for health care providers and patient safety in hospitals, implementation of safety culture with teamwork is an acceptable principle .This study aims to assess attitude of health care providers toward teamwork, safety climate and knowledge transfer through team collaboration at an educational medical center in . 2009. Method and materials : This was a descriptive study. All 225 resident physicians, nurses and other paramedics of an educational hospital of Tehran participated in the study. The tool for data collection was the Safety Attitudes Questionnaire (SAQ). Content validity and reliability of the questionnaire was assessed and confirmed. Data was analyzed using SPSS 16 and Chi square test . Results :The results demonstrated that 59% of nurses, 52% of physicians and 58%of paramedics believed that tasks are performing by teamwork. 30% of nurses, 21% of physicians and 39 % of paramedics had a sense of safety in workplace. 78% of nurses, 55 % of physicians and 73% of other paramedics believed that knowledge could transfer through team collaboration. Among demographic characteristics there were significant relationship between attitude of health care providers on teamwork with their marital status (p=0.001); attitude of health care providers on safety climate with their work experience (p=0.04); attitude of health care providers on knowledge transfer trough teamwork with organizational position (p=0.016). Conclusion : Attitude assessment of health care providers toward teamwork, safety climate and patients’ or health care providers’ safety is necessary to modify and improve the current deficits and to achieve to the culture of learning from errors. Managers can have an appropriate guide to establish safety culture with this sort of attitude assessments . Keywords : Teamwork, Safety Climate, Patient Safety, Knowledge Transfer. REFERENCES -Blegen M Pepper G Rosse J (2005). Safety climate on hospital units: A new measure. Advances in Patient Safety: From Research to Implementation, Agency for Health Research and Quality Safety. 4: 429-443. -Felknor SA et al (2000). Safety climate and its association with injuries and practices in public hospitals in Costa Rica . International Journal of Occupational and Environmental Health. 6 (1) 2-18. -Gerson RM et al (2000). Hospital safety climate and its relationship with safe work practices and work place exposure incident. AJIC: American Journal of Infection Control. 28 (3) 211-227. -Joint Comission on Accreditation of Health Care Organizations (2005). Hospital’s National Patient Safety Goals [on line] http://www.jointcommission.org/ [9July2012] -Kevin J et al (2008). Hospitalists use teamwork to improve care, increase efficiency in hospital .Human Resource Management Journal. 47 (3) 621-61. -Kaya S et al (2000). Variation in caregiver perceptions of teamwork climate and safety climate in a tertiary care hospital in Turkey .24th International Society for Quality in Health Care Conference. September 30 - October 3, 2007, Boston, USA. -Kohn LT et al (1999). To err is human: building a safer health system. A report of the committee on quality of health care in America ,Institute of Medicine .Washington DC .National Academy Press. Leonard M Graham S Bonacum D (2004). The human factor: the critical importance of effective teamwork and communication in providing safe care. Quality and Safety in Health Care. 13 (1) 85-90. Meterko M et al (2004). Teamwork culture and patient satisfaction in hospitals. Medical Care. 42(5) 492-498. Pronovost PJ Sexton B (2005). Assessing safety culture: Guidelines and recommendations. Quality and Safety in Health Care. 4 (14) 231-233. -Gershon R et al (2000). Hospital safety climate and its relationship with safe work practices and workplace exposure incidents. American Journal of Infection Control 28 (3) 211-221. -Rudman WJ et al (2006). Teamwork and safety culture in small rural hospitals in Mississippi. Patient Safety and Quality Healthcare, November/December 2006, Available Online: http://www.psqh.com/novdec06/mississppi.html. -Sexton JB et al (2000). Error ,stress and teamwork in medicine and aviation :cross sectional surveys. British Medical Journal. 320 (7237) 745-9 -Sexton JB et al (2003). The safety attitude questionnaire: guidelines for administration. The University of Texas Center of Excellence for Patient Safety Research and Practice, University of Texas, 99-108 -Sexton J B et al (2006). Variation in caregiver perceptions of teamwork climate in labor and delivery units. Journal of Perinatology. 26 (8) 463-70 -Shosteck K (2005). Improve patient safety Teamwork takes hold to. The Risk Management Reporters. 24 (1) 1-24. -Safety Attitude Questionnaire SAQ (2012) Team- work and safety climate, Texas University, Center for Health Care quality and safety [on line] http://www.uth.tmc.edu/schools/med/imed/patient_safety/documents/Survey-SAQTeamwork- Safety-Climate%20.pdf (23/7/2012) -Spencer M (2008). Safety climate surveys-experience from SPI [online] http//:www.wales.nhs.uk/sites3/docopen.cfm -Vincent C Taylor-Adams S Stanhope N (1998). Framework for analyzing risk and safety in clinical medicine. British Medical Journal. 316 (7138)1154-1157.